Becoming an Open Dialogue practitioner: a qualitative study of practitioners’ training experiences and transitioning to practice - Anestis, Eleftherios; Weaver, Timothy; Melia, Claire; Clarke, Katherine; Pilling, Steve (Frontiers in Psychology, 2024)
Introduction: In the context of transforming mental healthcare towards more personalised and recovery-oriented models, Open Dialogue has attracted significant international interest. Open Dialogue proposes a way of organizing services and delivering care that supports an immediate response to crisis, relational continuity of care, a social network approach and the empowerment of networks through shared decision-making and a flattened hierarchy. The ODDESSI trial currently being conducted in the UK is assessing the model's clinical and cost-effectiveness. Practitioners who delivered the approach within the trial undertook a one-year Open Dialogue foundation training program, however little is known about their training experiences. This study aimed to explore practitioners' experiences of receiving the training and transitioning to dialogic practice. Methods: Individual, joint and focus group interviews with 32 Open Dialogue practitioners were conducted. Thematic analysis was used to analyse the transcripts and transformational learning theory informed the interpretation of the findings.Results: Two themes further divided in subthemes were generated from the data: 1) experiences and impact of formal training and 2) becoming an Open Dialogue practitioner as an ongoing learning process beyond formal training: barriers and facilitators.Discussion: The one-year Open Dialogue foundation training was a transformative experience for participants due to its emphasis on self-work and its impact on a personal level. Practitioners felt adequately prepared by their training for dialogic practice, yet becoming an OD practitioner was seen as a continual process extending beyond formal training, necessitating ongoing engagement with the approach and organisational support. However, the commitment of participants to deliver optimal dialogic care was occasionally impeded by organisational constraints, resource limitations, and often having to concurrently deliver conventional care alongside Open Dialogue.